2020
DOI: 10.1051/0004-6361/201936574
|View full text |Cite
|
Sign up to set email alerts
|

Ellerman bombs and UV bursts: reconnection at different atmospheric layers

Abstract: The emergence of magnetic flux through the photosphere and into the outer solar atmosphere produces, amongst other dynamical phenomena, Ellerman bombs (EBs), which are observed in the wings of Hα and are due to magnetic reconnection in the photosphere below the chromospheric canopy. Signs of magnetic reconnection are also observed in other spectral lines, typical of the chromosphere or the transition region. An example are the UV bursts observed in the transition region lines of Si iv and the upper chromospher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 57 publications
9
40
2
Order By: Relevance
“…So, our results demonstrate that, in cancelling regions, a wide spectrum of ejections can be produced, with a wide range of different temperatures and sizes associated with Ellerman bombs, UV bursts and IRIS bombs and other hot and cool ejections (Yang et al 2013;Vissers et al 2015;Reid et al 2016;Rutten 2016;Nelson et al 2017;Rouppe van der Voort et al 2017;Young et al 2018;Tian et al 2018;Chen et al 2019;Guglielmino et al 2019;Ortiz et al 2020;Tiwari et al 2019;Huang et al 2019;Madjarska 2019). The predicted spatial offsets and time delays for hot and cool ejections are in accordance with observational findings.…”
Section: Discussionsupporting
confidence: 88%
“…So, our results demonstrate that, in cancelling regions, a wide spectrum of ejections can be produced, with a wide range of different temperatures and sizes associated with Ellerman bombs, UV bursts and IRIS bombs and other hot and cool ejections (Yang et al 2013;Vissers et al 2015;Reid et al 2016;Rutten 2016;Nelson et al 2017;Rouppe van der Voort et al 2017;Young et al 2018;Tian et al 2018;Chen et al 2019;Guglielmino et al 2019;Ortiz et al 2020;Tiwari et al 2019;Huang et al 2019;Madjarska 2019). The predicted spatial offsets and time delays for hot and cool ejections are in accordance with observational findings.…”
Section: Discussionsupporting
confidence: 88%
“…Bright flame-like emission in the wings of Hα, similar to that observed for Ellerman bombs, suggests a common reconnection origin, but the heating profile and the characteristics of the magnetic-field evolution may imply a somewhat different reconnection scenario (Rouppe van der Voort, Rutten, and Vissers, 2016). Similarly, UV bursts appear to be reconnection events that differ from both Ellerman bombs and quiet-Sun Ellerman-like brightenings in their magnetic topology, atmospheric penetration height, and energy, with the plasma in these events heated to transition-region temperatures (Nelson et al, 2017a;Young et al, 2018;Ortiz et al, 2020).…”
Section: Flux Emergence Into the Non-eruptive Solar Atmospheresupporting
confidence: 51%
“…Numerical simulations have shown that the magnetic topology that determines the height of reconnection along with the line of sight to the reconnection site play a role in the visibility of these small-scale heating events across the wavelength spectrum (Hansteen et al 2019;Peter et al 2019;Ortiz et al Movie associated to Fig. 5 is available at https:// www.aanda.org 2020; Syntelis & Priest 2020).…”
Section: Introductionmentioning
confidence: 99%